Environmental literacy portrait of pre-service science teacher in Indonesia - Vilmala, Berry Kurnia; Suhandi, Andi; Permanasari, Anna; Kaniawati, Ida; Purwanto, Hadi (Education and Development Research, 2023)
This article aims to picture the environmental literacy of the pre-service science teachers at Universitas Muhammadiyah Riau (UMRI). The highlighted environmental literacy consists of aspects of knowledge, attitudes and behavior of students related to environmental issues which are also part of the two themes of Educational for Sustainable Development (ESD), namely the theme of water and the theme of energy. Data were obtained through validated test items and questionnaire instruments. The results of this study obtained that students' environmental literacy was in the sufficient category, with an overall average percentage of environmental literacy for prospective science teacher students of 59.19. In addition, it was also obtained that the average percentage of environmental literacy of female students for the three aspects was higher than that of male students, although statistically it was concluded that there was no difference in environmental literacy of male students compared to female students. These results indicate that it is necessary to innovate lectures so that students' environmental literacy increases. One of the potential courses is Environmental Education which can be implemented on a project basis in accordance with the issues or themes in ESD.